1995
DOI: 10.1177/089124395009006008
|View full text |Cite
|
Sign up to set email alerts
|

Women's Military Roles Cross-Nationally

Abstract: This article outlines a theory of what affects the degree and nature of women's participation in the armed forces throughout history and across nations. Examining national security situations, military technology, military accession policies, demographic patterns, cultural values regarding gender, and structural patterns of gender roles, the article proposes a systematic theory of the conditions under which women's military roles expand and contract. The theory is then applied to analyze women's likely future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 15 publications
0
88
0
7
Order By: Relevance
“…Evidencia-se ainda a condicionante de o estudo ter sido realizado num contexto laboral onde as mulheres só conseguiram uma porta aberta há cerca de 30 anos. Trata-se da instituição militar, uma das instituições sociais mais prototipicamente masculina (Segal, 1995). Em Portugal, se desde os anos 1960 se podem encontrar algumas mulheres na vida militar, nomeadamente, na Força Aérea, foi apenas no início dos anos 1990 que as mulheres tiveram possibilidade de, em regime voluntário, se candidatarem à prestação de serviço militar.…”
Section: Precariedade E Mobilidade Geográfica E Os Seus Impactosunclassified
“…Evidencia-se ainda a condicionante de o estudo ter sido realizado num contexto laboral onde as mulheres só conseguiram uma porta aberta há cerca de 30 anos. Trata-se da instituição militar, uma das instituições sociais mais prototipicamente masculina (Segal, 1995). Em Portugal, se desde os anos 1960 se podem encontrar algumas mulheres na vida militar, nomeadamente, na Força Aérea, foi apenas no início dos anos 1990 que as mulheres tiveram possibilidade de, em regime voluntário, se candidatarem à prestação de serviço militar.…”
Section: Precariedade E Mobilidade Geográfica E Os Seus Impactosunclassified
“…For women to participate in the traditionally defined masculine institution of the military, the military had to transform and become more compatible for women or women had to change and become more seemingly suited to military service (Segal, 1995). Women embraced the changes, and the law granted them acceptance into the armed services; however, women encountered confusion and resistance from a military with a masculine culture.…”
Section: History Of Integrationmentioning
confidence: 99%
“…(Carreiras, 2006;Enloe, 1993;Kumar, 2004;Segal, 1993). These scholars have examined women's experiences in the armed forces (Carreiras, 2006), the militarisation of women's lives (Enloe, 1983(Enloe, , 2000, and women's military roles and participation (Segal, 1995). The study reported here draws on that foundation but diverges from it in two key directions.…”
Section: Issues Related To Women's Place In the Media And The Militarmentioning
confidence: 99%